2011
DOI: 10.1121/1.3643811
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of inducer continuity on auditory stream segregation: Comparison of physical and perceived continuity in different contexts

Abstract: The factors influencing the stream segregation of discrete tones and the perceived continuity of discrete tones as continuing through an interrupting masker are well understood as separate phenomena. Two experiments tested whether perceived continuity can influence the build-up of stream segregation by manipulating the perception of continuity during an induction sequence and measuring streaming in a subsequent test sequence comprising three triplets of low and high frequency tones (LHL-[ellipsis (horizontal)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Listeners' responses to the test sequences were consistent with the known effect of 11 frequency separation on stream segregation (e.g., van Noorden, 1975). As expected (Haywood & 12 Roberts, 2010, 2011b, the standard induction sequence had a strong segregation-promoting 13 effect, and the least streaming was observed for the no-induction condition. Also consistent with 14 the results of Haywood and Roberts (2010), reported segregation was significantly reduced 15 compared with the standard induction case when the 10 th (final) induction tone was replaced with 16 silence.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Listeners' responses to the test sequences were consistent with the known effect of 11 frequency separation on stream segregation (e.g., van Noorden, 1975). As expected (Haywood & 12 Roberts, 2010, 2011b, the standard induction sequence had a strong segregation-promoting 13 effect, and the least streaming was observed for the no-induction condition. Also consistent with 14 the results of Haywood and Roberts (2010), reported segregation was significantly reduced 15 compared with the standard induction case when the 10 th (final) induction tone was replaced with 16 silence.…”
supporting
confidence: 77%
“…auditory streaming experiments (Haywood & Roberts, 2010;2011a;2011b). This experiment 10 included the standard-and no-induction conditions that were used in Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work (Rogers and Bregman, 1993; Snyder et al, 2008, 2009b; Haywood and Roberts, 2011, 2013) has shown strong contextual effects of prior learning on auditory streaming. However, these studies of contextual influences on perception have typically involved within-session manipulations, and the perceptual effects have been probed using stimuli of rather short duration (generally <10 s).…”
Section: Methodsmentioning
confidence: 92%